(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
This review covers the various types of reinforcement phases of nanocomposites, such as nanoparticles, nanofibers, carbon nanotubes, and natural nanopigments, with a focus on the requirement of these materials, their production processes, and some current knowledge about their structure, properties, and potential applications. The necessity for such potential materials as well as other intriguing uses are perspectives. Applications of nanocomposites offer new technical and commercial potential for numerous sectors of the coating, automotive, electronics as solar cell, food packaging, and other industries because to their environmental friendliness. High performance materials with unique features include nanocomposites have a significant importance in the new advanced applications. Engineering plastics and elastomers have the fastest increasing requirement for fabrication as a nanocomposites with an expected annual growth rate of 25%. They are useful in a variety of applications, from packaging to biomedical ones, due to their great capabilities.